Emergent gambling advertising; a rapid review of marketing content, delivery and structural features - Torrance, Jamie (BMC Public Health, 2021)
BACKGROUND: Gambling advertising is well-funded and has become increasingly sophisticated in recent years. As the presence and pervasiveness of gambling advertising increases, there is a corresponding need for empirical understanding of the characteristics and trends associated with emergent gambling advertisements and marketing. However, there is limited data on this rapidly evolving phenomenon. METHODS: A rapid review was undertaken of the empirical research (2015–2020) that focused upon the content, delivery and structural features incorporated within emerging gambling advertising. RESULTS: Twenty-five studies were included in the review. The majority of these studies were conducted in either the UK or Australia; two jurisdictions that have unique and particularly liberal gambling environments. The literature suggests that emergent gambling advertising content is targeted, positively framed and in some instances, may overrepresent riskier bets. The sporting and social media spheres are densely populated with such advertisements that involve both direct and indirect marketing strategies. In relation to the online environment, there is evidence to suggest the emergence of more interactive advertisements that prompt user engagement. In addition, financial incentivisation has diversified and is often subject to strict and esoteric conditions. Despite these emergent trends, little provision is devoted to adequately displaying harm reductive or responsible gambling content within gambling advertising. CONCLUSIONS: Overall, there is a paucity of research and lack of methodological diversity concerning the characteristics of advertising within the literature. The barriers to investigating emerging gambling advertising are discussed alongside future research priorities. It is important for this research area to expand in order to appropriately inform ethical industry marketing and effective harm-reduction strategies. [Pre-registered online via Prospero: CRD42020184349]. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10805-w.